Determinants of dividend policy for public listed company in Malaysia / Nur Hidayati Sairin - Sairin, Nur Hidayati (2017)
The purpose of this study is to determine the determinants of dividend policy for public listed company in Malaysia. The factors that examine the dividend policy in this study are previous dividend payout ratio, net income, net cash flow, long-term debt to total asset and short-term debt to total asset. Data and methodology for this study were obtained from a relevant sources which is data stream. In this study, the total of listed company that being analyze is 70 companies with 10 different types of industry. The data being analyzing with stata software which include unit-root test, descriptive analysis, cross correlation and so on. The result from the findings shows that all of the five (5) variable have a relationship with the dividend policy. Where four (4) out of five (5) have a positive relationship which are the previous dividend pay-out ratio, net income, net cash flow and long-term debt to total asset. Meanwhile, the rest which is short-term debt to total asset have a negative relationship. Furthermore, the findings can be useful to future researcher in order to analysis whether all of the determinants still relevant to the dividend policy or not. Moreover, it also can help investor in making decisions while during investments activities. This study is actually extend from the empirical study from the previous researcher. The latest research on this study is last year which is 2016, but the researcher used timeframe within 2007 until 2011 only. So that, in this study the timeframe change into 2011 until 2016 with this we can see whether the determinants chosen still give impact to the dividend policy.